Revision of the subgenus Dicranomyia (Erostrata) Savchenko, 1976 (Diptera, Limoniidae) of Japan - Kato, Daichi; Tachi, Takuji; Gelhaus, Jon (Zootaxa, 2018)
The six Japanese species of the subgenus Dicranomyia (Erostrata) Savchenko, 1976 are revised. D. (E.) globithorax Osten Sacken, 1869 and D. (E.) tabashii (Alexander, 1934) are newly recorded from Japan. We elevate the two subspecies of D. globithorax to species rank based on distinct morphological differences. Three new species, D. (E.) reniformis sp. nov., D. (E.) submelas sp. nov., and D. (E.) yazuensis sp. nov. are described. The male genitalia of all Japanese species and female ovipositors of four of the six species are illustrated, and the habitus of adults are photographed. A key to the Japanese species of the subgenus is provided.